Kewenangan Pemerintah Kabupaten dalam SPBE: Tinjauan Yuridis Perda No. 6 Tahun 2020 - Zaidan Septiyo Nugroho; H.E Rakhmat Jazuli; Ahmad Rayhan (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The need for transparent governance in Tangerang Regency has been growing in line with the times. The implementation of the Electronic-Based Government System (SPBE) offers various benefits, such as easy access to public services without spatial or temporal limitations through the official website and the Tangerang Gemilang app, as well as the creation of more dynamic interactions between the government and the public. This study employs an empirical legal method to analyze the application of legal provisions in practice. The theories utilized include the theory of authority, which emphasizes the legitimacy of government actions based on laws and regulations, as well as the theory of public service, which focuses on the quality of services provided to the public. The research findings indicate that the SPBE in Tangerang Regency has a strong regulatory foundation and structure. However, the effectiveness of its implementation still faces various obstacles, such as limited human resources, uneven technological infrastructure, budget constraints, weak coordination among local government agencies, and low digital literacy among the public. These obstacles have prevented the goal of improving the quality of public services from being fully achieved, meaning that strong legal authority does not necessarily guarantee the effectiveness of services.